Effect of CO2/H2O on adsorptive removal of H2S/SO2 mixture. Issue 13 (7th June 2022) - Xuan, Jianyu; Wang, Chenyang; Zhang, Lin; Cui, Qun; Wang, Haiyan
ABSTRACT: Few studies focus on the simultaneous removal performance and mechanism of H2 S and SO2 mixture in Claus tail gas with a high concentration of H2 O (20–30 vol.%) and CO2 (8–10 vol.%). In this paper, the effects of H2 O and CO2 on the simultaneous removal of H2 S and SO2 for the by activated carbon (TL-1) were studied. Fresh (TL-1-F) and desulfurisation sulfur-loaded TL-1 activated samples (TL-1-E1 and TL-1-E2) were characterised by BET, elemental analysis, TG-MS, FT-IR and XPS. The simultaneous adsorption mechanism of H2 S and SO2 on TL-1 in the presence of H2 O and CO2 was discussed. Results show that the breakthrough sulfur capacity of TL-1 for the simultaneous removal of H2 S and SO2 mixture reaches up to 301.6 mg S/g ads when the feed gas containing 30 vol.% H2 O and 8 vol.% CO2, which is 40% higher than that without H2 O. H2 O in the feed is adsorbed on the surface of TL-1 and forms a water film. The adsorbed H2 S and SO2 are dissolved and ionised in the water film, which is conducive to the adsorption removal of H2 S and SO2 by TL-1 and the generation of sulfuric acid (55.8%) and S8 (44.2%). Meanwhile, CO2 is only physically adsorbed on the surface of TL-1, and does not participate in the chemical adsorption (or chemical reaction) for the removal sulfide process. GRAPHICAL ABSTRACT: UF0001